Analysis of an SVIC model with age-dependent infection and asymptomatic carriers. Issue 9 (4th July 2018) - Wang, Jinliang; Wu, Di; Sun, Hongquan
Abstract: In this paper, we formulated an age-dependent model for the transmission dynamics of HBV with vaccination. The class of acutely infectious individuals, asymptomatic carrier of host population is stratified by age. Mathematically, we established that basic reproduction number can govern the global stability of equilibria. Biologically, we verify the impacts of the asymptomatic carriers and the effectiveness of vaccination on the disease transmission through numerical simulation. Our results indicated that the more number of infectious individuals specific to frequently progressed to asymptomatic carriers, the more likely the disease can be eradicated by continuous vaccination strategies.